Penganekaragaman Konsumsi Pangan Berdasarkan Pola Pangan Harapan Di Wilayah Perdesaan Dan Perkotaan Kabupaten Serang - Sri Mulyati; Nanang Krisdianto (JURNAL AGRIBISNIS TERPADU, 2021)
Diversity of Food Consumption Based On Hope Food Patterns in Rural and Urban Area of Serang Regency. The objectives of the study are: To determine the diversity of food consumption based on the expected food patterns, the energy consumption of the people, what factors are hindering food diversification, formulate models for diversifying consumption patterns in rural and urban areas. The research is conducted in a span of 8 (eight) months, starting from May to December 2020. The study is conducted in Serang Regency, Banten Province. The research location is chosen deliberately. The research method used a survey, with sampling is cluster sampling, where 100 people as the sample taken (50 people in urban areas and 50 people in rural areas). The data collection method used is the 1x24 hour recall method and the frequency questionnaire method, then analyzed with the PPH software from the Food Security Agency. Data processing and analysis are carried out using the help of the SPSS (Statistical Product and Service Solution) and LISREL (Linear Structural Relationships) programs. The results showed that the levels of energy and protein consumption of respondents in rural areas were 90.60% and 110.46%, while in urban areas it was 93.21% and 124.27%. The energy consumption level for energy is in the medium category and the level of protein consumption is good. The diversity of food consumption based on PPH is still below the standard, namely PPH in rural areas 63.25 and urban areas 71.22.